Chlamydia trachomatis glyceraldehyde 3‐phosphate dehydrogenase: Enzyme kinetics, high‐resolution crystal structure, and plasminogen binding. (30th October 2020) - Schormann, Norbert; Campos, Juan; Motamed, Rachael; Hayden, Katherine L.; Gould, Joseph R.; Green, Todd J.; Senkovich, Olga; Banerjee, Surajit; Ulett, Glen C.; Chattopadhyay, Debasish
Abstract: Glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) is an evolutionarily conserved essential enzyme in the glycolytic pathway. GAPDH is also involved in a wide spectrum of non‐catalytic cellular 'moonlighting' functions. Bacterial surface‐associated GAPDHs engage in many host interactions that aid in colonization, pathogenesis, and virulence. We have structurally and functionally characterized the recombinant GAPDH of the obligate intracellular bacteria Chlamydia trachomatis, the leading cause of sexually transmitted bacterial and ocular infections. Contrary to earlier speculations, recent data confirm the presence of glucose‐catabolizing enzymes including GAPDH in both stages of the biphasic life cycle of the bacterium. The high‐resolution crystal structure described here provides a close‐up view of the enzyme's active site and surface topology and reveals two chemically modified cysteine residues. Moreover, we show for the first time that purified C . trachomatis GAPDH binds to human plasminogen and plasmin. Based on the versatility of GAPDH's functions, data presented here emphasize the need for investigating the Chlamydiae GAPDH's involvement in biological functions beyond energy metabolism.